2005
DOI: 10.1002/pssc.200461225
|View full text |Cite
|
Sign up to set email alerts
|

Porous silicon formation by HF chemical etching for antireflection of solar cells

Abstract: Macroporous and luminescent nanoporous Si are formed on Si wafers, which are modified with fine metal particles, by simply immersing the wafers in a HF solution without a bias or an oxidizing agent. The metal particles are deposited onto n-Si wafers by electroless displacement deposition from a metal salt solution including HF. The etching of Si consists of a local cathode reduction of oxygen and a local anode oxidation of Si. The porous layer is formed only on the metal-particle-deposited area of the Si wafer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 9 publications
2
52
0
Order By: Relevance
“…8d and e, conditions f and g, respectively). The structure change in the porous layer of multicrystalline n-Si by changing the photoillumination intensity and dissolved oxygen concentration is consistent with our previously reported results on single crystalline n-Si (Yae et al, 2005(Yae et al, , 2006b(Yae et al, , 2009). Table 1, respectively.…”
supporting
confidence: 81%
See 3 more Smart Citations
“…8d and e, conditions f and g, respectively). The structure change in the porous layer of multicrystalline n-Si by changing the photoillumination intensity and dissolved oxygen concentration is consistent with our previously reported results on single crystalline n-Si (Yae et al, 2005(Yae et al, , 2006b(Yae et al, , 2009). Table 1, respectively.…”
supporting
confidence: 81%
“…The metal-particle-assisted hydrofluoric acid etching can form both macroporous and microporous layers on multicrystalline Si wafers, which are modified with fine metal particles, by simply immersing the wafers in an hydrofluoric acid solution without a bias and a particular oxidizing agent (Yae et al 2006a(Yae et al , 2009. In previous papers, we reported that porous layer formation by this etching for 24 h decreased the reflectance of Si and increased the solar cell characteristics, which are not only photocurrent density but also photovoltage (Yae et al 2003(Yae et al , 2005(Yae et al , 2006a(Yae et al , 2009). …”
Section: Porous Silicon Formation By Metal-particle-assisted Hydroflumentioning
confidence: 99%
See 2 more Smart Citations
“…They have potential applications in photonic crystal devices (Yablonovitch, 1987), large-density magnetic recording devices (Chou et al, 1994), novel electronic devices (Schmidt & Eberl, 2001), synthesis of DNA electrophoresis mediate (Volkmuth & Austin, 1992),nanocontainers , surface-plasmon resonance biosensors (Brolo et al, 2004), antireflective coatings for solar cells (Yae et al, 2005), and etc. Such broad applications of nanostructures were intimately associated with their unique properties, which are sensitively dependent on their size and/or shape.…”
Section: Introductionmentioning
confidence: 99%